A Dime a Day : The Possibilities and Limits of Private Schooling in Pakistan - Andrabi, Tahir (Washington, DC : World Bank, 2012)
This paper looks at the private schooling sector in Pakistan, a country that is seriously behind schedule in achieving the Millennium Development Goals. Using new data, the authors document the phenomenal rise of the private sector in Pakistan and show that an increasing segment of children enrolled in private schools are from rural areas and from middle-class and poorer families. The key element in their rise is their low fees-the average fee of a rural private school in Pakistan is less than a dime a day (Rs.6). They hire predominantly local, female, and moderately educated teachers who have limited alternative opportunities outside the village. Hiring these teachers at low cost allows the savings to be passed on to parents through low fees. This mechanism-the need to hire teachers with a certain demographic profile so that salary costs are minimized-defines the possibility of private schools: where they arise, fees are low. It also defines their limits. Private schools are horizontally constrained in that they arise in villages where there is a pool of secondary educated women. They are also vertically constrained in that they are unlikely to cater to the secondary levels in rural areas, at least until there is an increase in the supply of potential teachers with the required skills and educational levels.